The influence of nanosecond microwave pulses on the regeneration processes - I. R. Knyazeva; M. A. Medvedev; L. P. Zharkova; A. A. Gostyukhina; O. P. Kutenkov; V. V. Rostov; M. A. Bolshakov (Бюллетень сибирской медицины, 2011)
The effects of pulse periodic microwaves (10 GHz, duration of pulse 100 ns, pulse repetition frequency 4—19 pps, peak power density 40—1 520 W/cm2 ) on the reparative regeneration of full-thickness skin wounds on mice was investigated. This effect depends on the pulse repetition frequency and peak power density.